Integrating Europe's Financial Markets - Decressin, Jorg (International Monetary Fund, 2007)
By and large, EU financial integration has been a success story. Still, the reform agenda is far from finished. What are the remaining challenges? What are the gains of closer financial market integration? This IMF book tracks the European Union's journey along the path to a single financial market and identifies the challenges and priorities that remain ahead. It pays particular attention to the most recent integration efforts in the European Union following the introduction of the euro. The study looks at the importance of financial integration, in particular for economic growth, the interplay between banks and markets, and equity market integration. It closely examines the relationship between financial integration and financial stability. This interaction presents the European Union with a challenge, but also with the opportunity to play a pioneering role in developing a regional approach to financial stability that could provide lessons for the rest of the world.